Bisphenol A and chlorinated derivatives of bisphenol A assessment in end stage renal disease patients: Impact of dialysis therapy - Guillaume Cambien; Antoine Dupuis; Mohamed Belmouaz; Marc Bauwens; Astrid Bacle; Stéphanie Ragot; Virginie Migeot; Marion Albouy; Sarah Ayraud-Thevenot (Ecotoxicology and Environmental Safety, 2024)
Patients with end stage kidney disease treated by dialysis (ESKDD) process dialysis sessions to remove molecules usually excreted by kidneys. However, dialysis therapy could also contribute to endocrine disruptors (ED) burden. Indeed, materials like dialyzer filters, ultrapure dialysate and replacement fluid could exposed ESKDD patients to Bisphenol A (BPA) and chlorinated derivatives of BPA (ClxBPAs). Thus, our aim was to compare BPA and ClxBPAs exposure between ESKDD patients, patients with stage 5 chronic kidney disease (CKD5) not dialyzed and healthy volunteers. Then we describe the impact of a single dialysis session, according to dialysis modalities (hemodialysis therapy (HD) versus online hemodiafiltration therapy (HDF)) and materials used with pre-post BPA and ClxBPAs concentrations. The plasma levels of BPA and four ClxBPAs, were assessed for 64 ESKDD patients in pre and post dialysis samples (32 treated by HD and 32 treated by HDF) in 36 CKD5 patients and in 24 healthy volunteers. BPA plasma concentrations were 22.5 times higher for ESKDD patients in pre-dialysis samples versus healthy volunteers (2.208 ± 5.525 ng/mL versus 0.098 ± 0.169 ng/mL) (p < 0.001). BPA plasma concentrations were 16 times higher for CKD5 patients versus healthy volunteers, but it was not significant (1.606 ± 3.230 ng/mL versus 0.098 ± 0.169 ng/mL) (p > 0.05). BPA plasma concentrations for ESKDD patients in pre-dialysis samples were 1.4 times higher versus CKD5 patients (2.208 ± 5.525 ng/mL versus 1.606 ± 3.230 ng/mL) (p < 0.001). For healthy volunteers, ClxBPAs were never detected, or quantified while for CKD5 and ESKDD patients one ClxBPAs at least has been detected or quantified in 14 patients (38.8%) and 24 patients (37.5%), respectively. Dialysis therapy was inefficient to remove BPA either for HD (1.983 ± 6.042 ng/mL in pre-dialysis versus 3.675 ± 8.445 ng/mL in post-dialysis) or HDF (2.434 ± 5.042 ng/mL in pre-dialysis versus 7.462 ± 15.960 ng/mL in post dialysis) regarding pre-post BPA concentrations (p > 0.05). The same result was observed regarding ClxBPA analysis. Presence of polysulfone in dialyzer fibers overexposed ESKDD patients to BPA in pre-dialysis samples with 3.054 ± 6.770 for ESKDD patients treated with a polysulfone dialyzer versus 0.708 ± 0.638 (p = 0.040) for ESKDD patients treated without a polysulfone dialyzer and to BPA in post-dialysis samples with 6.629 ± 13.932 for ESKDD patients treated with a polysulfone dialyzer versus 3.982 ± 11.004 (p = 0.018) for ESKDD patients treated without a polysulfone dialyzer. This work is to our knowledge the first to investigate, the impact of a dialysis session and materials used on BPA and ClxBPAs plasma concentrations and to compare these concentrations to those found in CKD5 patients and in healthy volunteers.